The power of pragmatism : knowledge production and social inquiry - Wills, Jane; Lake W. Robert (Manchester University Press, 2020)
This book makes the case for a pragmatist approach to the practice of social inquiry and knowledge production. Through diverse examples from multiple disciplines, contributors explore the power of pragmatism to inform a practice of inquiry that is democratic, community-centred, problem-oriented and experimental. Drawing from both classical and neo-pragmatist perspectives, the book advances a pragmatist sensibility in which truth and knowledge are contingent rather than universal, made rather than found, provisional rather than dogmatic, subject to continuous experimentation rather than ultimate proof, and verified in their application in action rather than in the accuracy of their representation of an antecedent reality. The Power of Pragmatism offers a path forward for mobilizing the practice of inquiry and knowledge production on behalf of achieving what Dewey called a sense for the better kind of life to be led.